Developing a core outcome set for periodontal trials - Lamont, Thomas J.; Clarkson, Jan E.; Ricketts, David N. J.; Heasman, Peter A.; Ramsay, Craig R.; Gillies, Katie (PloS one, 2021)
There is no agreement which outcomes should be measured when investigating interventions for periodontal diseases. It is difficult to compare or combine studies with different outcomes; resulting in research wastage and uncertainty for patients and healthcare professionals. Develop a core outcome set (COS) relevant to key stakeholders for use in effectiveness trials investigating prevention and management of periodontal diseases. Mixed method study involving literature review; online Delphi Study; and face-to-face consensus meeting. Key stakeholders: patients, dentists, hygienist/therapists, periodontists, researchers. The literature review identified 37 unique outcomes. Delphi round 1: 20 patients and 51 dental professional and researchers prioritised 25 and suggested an additional 11 outcomes. Delphi round 2: from the resulting 36 outcomes, 13 patients and 39 dental professionals and researchers prioritised 22 outcomes. A face-to-face consensus meeting was hosted in Dundee, Scotland by an independent chair. Eight patients and six dental professional and researchers participated. The final COS contains: Probing depths, Quality of life, Quantified levels of gingivitis, Quantified levels of plaque, Tooth loss. Implementation of this COS will ensure the results of future effectiveness trials for periodontal diseases are more relevant to patients and dental professionals, reducing research wastage. This could reduce uncertainty for patients and dental professionals by ensuring the evidence used to inform their choices is meaningful to them. It could also strengthen the quality and certainty of the evidence about the relative effectiveness of interventions. COMET Database: http://www.comet-initiative.org/studies/details/265?result=true.